Correlation between HbA1c and TG/HDL Ratio with eGFR in Type 2 Diabetes Mellitus Patients in Risa Sentra Medika Hospital Mataram - Lestari, Novianti Anggie; Lestarini, Ima Arum; Kusuma, Yan Adhitya (Jurnal Biologi Tropis, 2026)
One of the main causes of declining kidney function is type 2 diabetes mellitus (DM2), which is typified by a drop in the estimated glomerular filtration rate (eGFR). The triglyceride-to-HDL (TG/HDL) ratio indicates atherogenic dyslipidemia, which contributes to the development of diabetic nephropathy, whereas HbA1c represents long-term glycemic management. This study aimed to analyze the correlation between HbA1c and TG/HDL ratio with eGFR in DM2 patients in Mataram. A cross-sectional analytical study was conducted involving 56 patients at Risa Sentra Medika Hospital from Juli to Desember 2025. Laboratory data were used to gather information on HbA1c, triglycerides, HDL, serum creatinine, and eGFR. The correlation between the variables was evaluated using regression analysis and Pearson correlation. The eGFR was 78.37 ml/min/1.73 m², the TG/HDL ratio was 5.84, and the mean HbA1c was 9.21%. The TG/HDL ratio had a very weak positive connection with eGFR (r = 0.143), but HbA1c had a very poor negative correlation (r = -0.037). According to regression analysis, neither variable was statistically significant (p>0.05) and only explained 2.2% of the variation in eGFR (R2 = 0.022). among conclusion, among patients with DM2, there was no discernible relationship between HbA1c and the TG/HDL ratio with eGFR.